Concealed - Gonzalez, Christina Diaz, 1969- (Scholastic Inc., 2021)
Katrina's family is in witness protection, so she knows it's only a matter of time before they have to move on and assume new identities. But when their location leaks, her parents go missing and Katrina is forced to embark on a dangerous rescue mission with her new friend, Parker. Soon, Katrina discovers shocking secrets about her own past, and she learns the truth about her broken memories.